Improved metabolic health among the obese in six population surveys 1986 to 2009: the Northern Sweden MONICA study - Benckert, Martin (BMC Obes, 2015)
BACKGROUND: The incidence of CVD is decreasing in spite of increasing BMI in the population. We examined trends in metabolic health among overweight and obese individuals and the influence of lifestyle and socioeconomic status. Six cross sectional population surveys in the Northern Sweden MONICA Study between 1986 and 2009. 8 874 subjects 25 to 64 years participated (74% participation rate). Metabolic health was defined as a total cholesterol level below 5.0 mmol/l, blood pressure below 140/90 mmHg and not having diabetes. In 2009 the age span 25 to 74 years was studied. RESULTS: The prevalence of metabolic health among obese subjects increased by 7.9 % per year (95% confidence interval 5.4; 10.5), reaching 21.0% in 2009. The corresponding figures for overweight subjects were 5.9% per year (4.6; 7.3), reaching 18% in 2009, whereas for the normal-weight subjects, the increase was 6.2% per year (5.3; 7.2), reaching 39% in 2009. The prevalence of metabolic health among subjects with abdominal obesity increased by 5.8% (4.6; 7.0) per year, reaching 17.3% in 2009. Among those with no abdominal obesity the increase was 6.2% (5.2; 7.1), reaching 38% in 2009 (p = <0.001 for all groups). Only among non-obese men and obese women did the increase continue between 2004 and 2009. In the other groups a slight decline or levelling off was noted. In 2009 women had a 27% higher prevalence of metabolic health than men. The prevalence of metabolic health among the obese was 19.8% which declined to 15.8% if subjects treated for hypertension or hypercholesterolemia were classified as not healthy. Overweight and obese subjects were less often metabolically healthy (odds ratio 0.54 and 0.59 respectively) compared with normal-weight subjects, independent of sex and age as were subjects with abdominal obesity (odds ratio 0.52). Adjustments for smoking, physical activity and education level did not influence any estimates. CONCLUSIONS: This report shows a large increase in prevalence of metabolic health from 1986 to 2009 for all anthropometric categories. Metabolic health remains considerably less prevalent among overweight and obese subjects than among those with normal weight.